Reconceptualising the Principle of Non-Refoulement in the Context of Climate-Induced Migration: Navigating through International Obligations - Md Tarik Morshed; Mumtahena Ferdousy (Dhaka University Law Journal, 2025)
The novelty and complexity of climate-induced migration are increasingly challenging the established domains of international human rights and refugee law worldwide. It is widely established that the current international legal frameworks are inadequate in addressing the protection needs of migrant people due to climate change. This article examines how the reinterpretation of the principle of non-refoulement, primarily articulated in Article 33 of the 1951 Refugee Convention and expanded through international human rights instruments, can protect those migrated by climate-induced harms. Drawing on international treaties, instruments, and case laws, this article argues that climate-related harm can be addressed within the broader frameworks of human rights and refugee law through the reinterpretation of key legal concepts. In addition to addressing other issues, the article criticises the prevailing emphasis on ‘imminence’ in international refugee and human rights law. It proposes a more nuanced approach that considers the severity and foreseeability of climate-related threats. It concludes that a human rights-based and forward-looking legal response is necessary to minimise the protection gap for individuals displaced by climate change. Dhaka University Law Journal, 2025, 36 (1), 101-121